Developing high throughput quantitative PCR assays for diagnosing Ikeda and other Theileria orientalis types common to New Zealand in bovine blood samples. Issue 1 (2nd January 2016) - Pulford, DJ; Gias, E; Bueno, IM; McFadden, AMJ
Abstract: AIMS: To develop rapid, quantitative PCR (qPCR) assays using high resolution melt (HRM) analysis and type-specific TaqMan assays for identifying the prevalent types of Theileria orientalis found in New Zealand cattle; and to evaluate their analytical and diagnostic characteristics compared with other assays for T. orientalis . METHODS: Nucleotide sequences aligned with T. orientalis Buffeli, Chitose and Ikeda types, obtained from DNA extracted from blood samples from infected cattle, were used to design HRM and type-specific probe-based qPCR assays. The three type-specific assays were also incorporated into a single-tube multiplex qPCR assay. These assays were validated using DNA extracted from blood samples from cattle in herds with or without clinical signs of T. orientalis infection, other veterinary laboratory samples, as well as plasmids containing T. orientalis type-specific sequences. Diagnostic specificity (DSp) and sensitivity (DSe) estimates for the qPCR assays were compared to blood smear piroplasm results, and other PCR assays for T. orientalis . Copy number estimates of Ikeda DNA in blood were determined from cattle exhibiting anaemia using the Ikeda-specific qPCR assay. RESULTS: The T. orientalis type-specific and the HRM qPCR assays displayed 100% analytical specificity. The Ikeda-specific qPCR assay exhibited linearity (R 2  = 0.997) with an efficiency of 94.3%. Intra-assay CV were ≤0.08 and inter-assay CV were ≤0.095. For blood samples from cows with signs of infection with T. orientalis, the DSp and DSe of the multiplex probe qPCR assay were 93 and 96%, respectively compared with blood smears, and 97 and 100%, respectively compared with conventional PCR assays. For the Ikeda-specific qPCR assay, the number of positive samples (n=66) was slightly higher than a conventional PCR assay (n=64). The concentration of Ikeda genomes in blood samples from 41 dairy cows with signs of infection with T. orientalis ranged between 5.6 × 10 4 and 3.3 × 10 6 genomes per µL of blood. CONCLUSIONS: All qPCR assays had improved specificity and sensitivity over existing conventional PCR assays for diagnosis of T. orientalis Ikeda. The burden of Ikeda DNA in blood was demonstrated using an Ikeda-specific qPCR assay with titrated synthetic gene target. CLINICAL RELEVANCE: Adoption of high-throughput DNA extraction and qPCR reduced T. orientalis and Ikeda diagnosis times. The Ikeda-specific qPCR assay provides a specific diagnosis for Ikeda in animals with signs of infection with T. orientalis and can be used to monitor the parasite load of Ikeda in blood.